ANALISIS PROFITABILITAS PERUSAHAAN DAERAH AIR MINUM (PDAM) KUTAI BARAT - Adi Suroso, Windy Finati Sari, Titin Ruliana (EKONOMIA, 2015)
The problem in this study is whether viewed from the aspect Profitability Net Profit Margin, Return on Investment, and Return On Equity Regional Water Company Kutai Barat in 2014 increased compared to the year 2013.The method used in this study focused on the Regional Water Company Kutai Barat that focuses on the financial statements to see the growth of the company's profitability in 2013 and 2014. The report is used to analyze the level in managing the financial statements are measured from the ratio of profitability (profitability ratios ) from the aspect of net profit margin, return on investment , and return on equity at the Regional Water Company Kutai Barat in 2013 and 2014. Basic theory used is Management Accounting by using financial ratio analysis.Based on the analysis of the results of research conducted as follows: The ratio of net profit margin in 2013 amounted to (92.3%) and in 2014 of (119.64%) indicate that the net profit margin in 2014 has not increased compared to 2013. The ratio of Return On Investment in 2013 amounted to (10.04%) and in 2014 amounted to (16.28%) indicate that the return on investment as the year 2014 has not increased compared to 2013. The ratio of return on equity as the year 2013 amounted to (10.34%) and the 2014 amounting to (17.34%) showed that the return on equity in 2014 has not increased compared to 2013